Ceftazidime-Avibactam Use for Klebsiella pneumoniae Carbapenemase–Producing K. pneumoniae Infections: A Retrospective Observational Multicenter Study. (22nd February 2021) - Tumbarello, Mario; Raffaelli, Francesca; Giannella, Maddalena; Mantengoli, Elisabetta; Mularoni, Alessandra; Venditti, Mario; De Rosa, Francesco Giuseppe; Sarmati, Loredana; Bassetti, Matteo; Brindicci, Gaetano; Rossi, Marianna; Luzzati, Roberto; et al.
Abstract: Background: A growing body of observational evidence supports the value of ceftazidime-avibactam (CAZ-AVI) in managing infections caused by carbapenem-resistant Enterobacteriaceae. Methods: We retrospectively analyzed observational data on use and outcomes of CAZ-AVI therapy for infections caused by Klebsiella pneumoniae carbapenemase–producing K. pneumoniae (KPC-Kp) strains. Multivariate regression analysis was used to identify variables independently associated with 30-day mortality. Results were adjusted for propensity score for receipt of CAZ-AVI combination regimens versus CAZ-AVI monotherapy. Results: The cohort comprised 577 adults with bloodstream infections (n = 391) or nonbacteremic infections involving mainly the urinary tract, lower respiratory tract, and intra-abdominal structures. All received treatment with CAZ-AVI alone (n = 165) or with ≥1 other active antimicrobials (n = 412). The all-cause mortality rate 30 days after infection onset was 25% (146/577). There was no significant difference in mortality between patients managed with CAZ-AVI alone and those treated with combination regimens (26.1% vs 25.0%, P = .79). In multivariate analysis, mortality was positively associated with presence at infection onset of septic shock ( P = .002), neutropenia ( P < .001), or an INCREMENT score ≥8 ( P = .01); with lower respiratory tract infection (LRTI) ( P = .04); and with CAZ-AVI dose adjustment for renal function ( P = .01). Mortality was negatively associated with CAZ-AVI administration by prolonged infusion ( P = .006). All associations remained significant after propensity score adjustment. Conclusions: CAZ-AVI is an important option for treating serious KPC-Kp infections, even when used alone. Further study is needed to explore the drug's seemingly more limited efficacy in LRTIs and potential survival benefits of prolonging CAZ-AVI infusions to ≥3 hours. Abstract : We retrospectively analyzed observational data on the use and outcomes of ceftazidime-avibactam (CAZ-AVI) therapy for infections causedby Klebsiella pneumoniae carbapenemase–producing K. pneumoniae (KPC-Kp) in 22 hospitals in Italy. CAZ-AVI appears to be an important drug for treatment of serious KPC-Kp infections, even when used alone.